If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(t + -3) + 6t = 8t + -4 Reorder the terms: -3(-3 + t) + 6t = 8t + -4 (-3 * -3 + t * -3) + 6t = 8t + -4 (9 + -3t) + 6t = 8t + -4 Combine like terms: -3t + 6t = 3t 9 + 3t = 8t + -4 Reorder the terms: 9 + 3t = -4 + 8t Solving 9 + 3t = -4 + 8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8t' to each side of the equation. 9 + 3t + -8t = -4 + 8t + -8t Combine like terms: 3t + -8t = -5t 9 + -5t = -4 + 8t + -8t Combine like terms: 8t + -8t = 0 9 + -5t = -4 + 0 9 + -5t = -4 Add '-9' to each side of the equation. 9 + -9 + -5t = -4 + -9 Combine like terms: 9 + -9 = 0 0 + -5t = -4 + -9 -5t = -4 + -9 Combine like terms: -4 + -9 = -13 -5t = -13 Divide each side by '-5'. t = 2.6 Simplifying t = 2.6
| 5x+1=3x+35 | | 24=3x+2 | | 0.1(x+40)+0.1=5 | | 3/5x=-6 | | 7(3x-7)-2=21x-51 | | 4x+16=x+28 | | 8z-6=z/2+9 | | 3(x+3)-4whenx=4 | | .7(b+3)+4=25+7b | | 23+6= | | R(7+1)=50 | | 1/2x=1/10x+4/5 | | x+0.5=3.5 | | 9x+8=9(x-1) | | P/13=4 | | y=-8/6x-16 | | x/8+2=x/8 | | x^(5/2)=32 | | x*50=130 | | -5/6(12-6x) | | -6-[(-3-6)+15]-16= | | 13=k/6 | | 3x-12+4x-12-7x+13=19 | | 96=X*54 | | 2x^2+3x^2=3 | | 7=k/6 | | 3m^2-2=-5m | | 8p/2p-7=32 | | -79= | | 10x^2-20x-26=0 | | 0.75x+.05(12-x)=.10(76) | | x/36+5=33 |